Pelatihan Budidaya Maggot pada Anak Asuh di Panti Asuhan Muhammadiyah Malang: Maggot Cultivation Training on Foster Child on Muhammadiyah Orphanage, Malang - Noer Rahmi Ardiarini; Muhamad Firdaus; Eko Widodo; Zulfaidah Penata Gama; Anang Sujoko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Muhammadiyah Malang Orphanage (PAMMA) is one of the Da'wah movements of Amar Ma'ruf Nahi Munkar in the municipality of Malang, in the social sector, through alleviating education and empowering school-aged orphans. One of the empowerment programs is to provide life skills to foster children. PAMMA has land that can be used for fruit and vegetable cultivation, chicken, and fish. However, the cultivation of chicken and fish requires the availability of expensive commercial feed. Maggot is a black fly caterpillar rich in nutrients and protein and can be used as a substitute for chicken and fish feed. The purpose of this activity is training for foster children and orphanage caregivers to cultivate maggots, and the results are used as an alternative to chicken and fish feed. The method of this service activity is in the form of training, implementation, monitoring, and evaluation of activities. Maggot cultivation training at the Integrated Waste Disposal Site, Tumpang, Malang district. Maggot cultivation practices are carried out on PAMMA land. Several foster children and orphanages had received training and practiced maggot cultivation. Under caregivers' guidance, foster children have successfully cultivated maggots independently at PAMMA by utilizing organic waste obtained from the scope of the orphanage. Cultivated caterpillars have been used as a substitute for commercial chicken and fish feed. The conclusion is the training on maggot production has been carried out and mastered by the PAMMA brothers and caregivers, and the production has been used as feed for chicken and fish cultivation.